Panics - Molinard, Barbara, 1921-1986; Ramadan, Emma (New York City : The Feminist Press, 2022)
"A collection of thirteen short stories about sickness, death, mental illness, and control by French author Barbara Molinard (1921-1986), who destroyed much of her writing while still alive"--
First published in French as Viens by Éditions Mercure de France in 1969.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Text in English, translated from French.
eBooks on EBSCOhost
Keywords: Molinard, Barbara, -- 1921-1986 -- Translations into English; FICTION; Short stories, French; short stories; Short stories; Nouvelles